A review: can waste wool keratin be regenerated as a novel textile fibre via the reduction method?. Issue 8 (25th July 2022) - Lebedytė, Milda; Sun, Danmei
Abstract: In the mid-twentieth century, natural fibre shortages spurred research into regenerated protein fibres, including research into regenerated wool keratin. Although these materials were soon displaced by outperforming synthetic fibres, today's global shifts towards an eco-friendlier, more environmentally aware, sustainable fashion industry have increased interest into such materials. This paper discusses the theory behind chemically recycling wool (keratin) from textile waste via a mixed solvent system that employs reduction, one of the several possible methods, and then wet spinning of a blended keratin solution to create a novel filament. The scope is to create a high value product that could help close the loop of the wool textile industry. Chemical wool recycling is suggested as a complementary process to the already existing mechanical wool recycling methods, as it can be used for materials that cannot be processed mechanically. It is generally recognised that regenerated wool keratin has poor mechanical stability and if used for textile production would most likely exist in blends with other materials and require post-processing to improve performance. These novel materials could displace some of the currently dominant fibres on the textile market and therefore help mitigate some the negative environmental impacts of the fashion industry, provided they meet eco-friendly credentials in their manufacture and end-of-life. The chemical principles outlined herein can be in many cases applied to other keratinaceous waste streams such as non-edible animal products (horns, hooves), feathers and, importantly, other (non-textile) sources of wool.